2018
DOI: 10.1111/jcpp.12910
|View full text |Cite
|
Sign up to set email alerts
|

Why do children read more? The influence of reading ability on voluntary reading practices

Abstract: Background: This study investigates the causal relationships between reading and print exposure and investigates whether the amount children read outside school determines how well they read, or vice versa. Previous findings from behavioural studies suggest that reading predicts print exposure. Here, we use twin-data and apply the behaviourgenetic approach of direction of causality modelling, suggested by Heath et al. (1993), to investigate the causal relationships between these two traits. Method: Partial dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 41 publications
11
73
1
Order By: Relevance
“…This suggests the effect ran from reading skill to print exposure between the ages of 10 and 11 years (Harlaar, Deater‐Deckard, Thompson, DeThorne, & Petrill, ). Likewise, a recent study utilizing direction of causality models concluded that it was reading ability driving print exposure (Van Bergen et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the effect ran from reading skill to print exposure between the ages of 10 and 11 years (Harlaar, Deater‐Deckard, Thompson, DeThorne, & Petrill, ). Likewise, a recent study utilizing direction of causality models concluded that it was reading ability driving print exposure (Van Bergen et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the FLRAS explained unique variance in L1 word decoding directly and L1 word decoding explained variance in print exposure. This finding is unsurprising because L1 reading researchers have found that individual differences in reading ability predicts individual differences in print exposure (van Bergen et al, ). In addition, individual differences in L1 print exposure have predicted unique variance in L2 proficiency (Sparks et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Passive gene-environment correlations may explain well-established associations between home characteristics and child outcomes. Examples thereof are, the association between the number of books in the home and children's reading skills (van Bergen et al 2018;Sikora et al 2019) and the association between household chaos and children's problem behaviour (Coldwell et al 2006). What is needed is a design that controls for children's genetic propensities to demonstrate genuine family environmental influences.…”
Section: Introductionmentioning
confidence: 99%